2015
DOI: 10.1073/pnas.1508593112
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational neural mediators of early-life anxious temperament

Abstract: Understanding the heritability of neural systems linked to psychopathology is not sufficient to implicate them as intergenerational neural mediators. By closely examining how individual differences in neural phenotypes and psychopathology cosegregate as they fall through the family tree, we can identify the brain systems that underlie the parent-to-child transmission of psychopathology. Although research has identified genes and neural circuits that contribute to the risk of developing anxiety and depression, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
152
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(166 citation statements)
references
References 47 publications
13
152
1
Order By: Relevance
“…Notably, the offspring of those rats also showed significantly increased BDNF methylation, illustrating the perpetuation of the negative effects of stress across generations. Studies in primates have also clearly documented that variations in patterns of maternal rearing can lead to distinct epigenetic signatures that effect how an individual’s DNA is read in specific brain regions compared to DNA present in blood cells (Fox et al 2015; Provencal et al 2012). Given the spatial and temporal complexity of gene expression during early human brain development (Kang et al 2011), it is clear that maternal stress during pregnancy and beyond can have intergenerational consequences.…”
Section: Biological Mechanismsmentioning
confidence: 99%
“…Notably, the offspring of those rats also showed significantly increased BDNF methylation, illustrating the perpetuation of the negative effects of stress across generations. Studies in primates have also clearly documented that variations in patterns of maternal rearing can lead to distinct epigenetic signatures that effect how an individual’s DNA is read in specific brain regions compared to DNA present in blood cells (Fox et al 2015; Provencal et al 2012). Given the spatial and temporal complexity of gene expression during early human brain development (Kang et al 2011), it is clear that maternal stress during pregnancy and beyond can have intergenerational consequences.…”
Section: Biological Mechanismsmentioning
confidence: 99%
“…This trait-like disposition, termed anxious temperament (AT), is a prominent childhood risk factor for the later development of anxiety disorders, depression, and comorbid substance abuse (1721). With our nonhuman primate model, we identified the altered neural circuitry that underlies the development of AT and found that it is similar to that observed in humans with anxiety disorders (3, 8, 10, 22). This neural systems level information provides the critical groundwork for directly testing regionally specific molecular hypotheses potentially important in the pathophysiology of AT.…”
Section: Introductionmentioning
confidence: 60%
“…The findings regarding the OPro/AI region may be particularly relevant as this region of the prefrontal cortex is highly connected with the amygdala (87). We recently demonstrated in a sample of 592 young rhesus monkeys that NEC-related glucose metabolism in the OPro/AI region (along with the bed nucleus of the stria terminalis (BST) and the periaqueductal gray (PAG)) correlated with AT and was heritable (10). Importantly, brain metabolism in these regions was also genetically correlated with AT, which implies the involvement of similar genes in mediating AT and altered brain function in OPro/AI, BST, and PAG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Fox et al . measured FDG-PET and behavioral responses during a well-standardized task of threat processing in a large familial sample of preadolescent rhesus monkeys [9]. The authors computed heritability of brain metabolism, heritability of a behavioral anxiety phenotype, and the bivariate heritability of both phenotypes, then conducted voxelwise bivariate genetic correlations , and found strong associations between metabolism in a prefrontal-limbic-midbrain circuit and anxious behavior.…”
mentioning
confidence: 99%